Doktrin Manusia dan Dosa - Angel; Alma; Delsa Natalia; Dhea Ananta; Sarmauli (CV Edujavare Publishing, 2025)
This paper present a theological examination of the nature of humanity and the doctrine of sin within the framework of Christian thought, with particular emphasis on biblical foundations. According Scripture, human beings were created in the imago Dei-bearing the image and likeness of God-but subsequently fell into sin trought deliberate disobedience. This fall resulted in a fractured relationship with God, interpersonal alienation, and disorder within the created order. The study systematically analyzes, the origin, nature, and consequences of sin, while also addressing the redemptive provision offered trought the person and work of Jesus Christ. The aim is to foster a deeper theological comprehension of humanity’s fallen condition and the transformative power of divine grace. In doing so, the paper seeks to encourage a life of continual repentance, spiritual renewal, and faithfull obedience in response to God’s salvific intiative.